2021
DOI: 10.3390/polym13050717
|View full text |Cite
|
Sign up to set email alerts
|

Water-Borne ZnO/Acrylic Nanocoating: Fabrication, Characterization, and Properties

Abstract: This work aims to explore how ZnO nanoparticles enhance the mechanical, photoaging, and self‑cleaning properties of water‑borne acrylic coating. Micro/nano‑ZnO particles (at 2 wt.% of total solid resin) were dispersed into the acrylic polymer matrices using ultrasonication to understand the effect of the size of the coating properties. The effect of ZnO particles on the properties of composite coatings (25 µm of thick) have been evaluated through various tests, such as abrasion measurement, ultraviolet/condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…In the presence of 2 wt% ZnO-Ag nanohybrids, the conversion of the acrylate groups is affected by photocatalytic characteristic of nano ZnO-Ag hybrid structure. This effect is similar to the case of photocatalyst nanoparticles (A-TiO 2 , ZnO) [34][35][36][37]. The difference is that due to the hybridization with Ag, the photocatalytic activity of ZnO is reinforced.…”
Section: Hardness Evaluationsupporting
confidence: 69%
“…In the presence of 2 wt% ZnO-Ag nanohybrids, the conversion of the acrylate groups is affected by photocatalytic characteristic of nano ZnO-Ag hybrid structure. This effect is similar to the case of photocatalyst nanoparticles (A-TiO 2 , ZnO) [34][35][36][37]. The difference is that due to the hybridization with Ag, the photocatalytic activity of ZnO is reinforced.…”
Section: Hardness Evaluationsupporting
confidence: 69%
“…It was believed that the addition of nano-TiO 2 as photocatalyst into cement-based material has won great attention and wide applications in large-scale due to its features in terms of chemical stability, high photocatalytic activity, low price, easy availability, high dielectric constant, weather ability, antimicrobial prosperities, and stability under UV radiation, and the problem of urban air pollutants was solved due to its self-cleaning, self-disinfecting, and air purifying properties, contributing to the environmental pollution cleansing [20,21,53,72,73].…”
Section: Titanium Oxide Nanoparticlesmentioning
confidence: 99%
“…Additionally, several research papers have discussed the effect of ZnO NPs on the mechanical properties of different coatings. ZnO NPs added into acrylic coating (Vu et al, 2021), polyurethane acrylate coating (Ariffin et al, 2020), and alkyd coating (Sturdy et al, 2020) showed an improvement in the mechanical properties of the coatings. To our knowledge, the effect of ZnAl 2 O 4 NPs on the mechanical properties of epoxy coating has not been previously studied.…”
Section: Introductionmentioning
confidence: 97%